Economic efficient method for the design of computer classes with the use of information technology (Journal of Mathematics Mechanics and Computer Science, 2015)
This article is devoted to the organization of computer classrooms of the University, in accordance with the modern methods and technologies of it industry, such as virtualization, cloud-based data storage technologies, network software, etc. Information technology (IT) industry in accordance with existing methods and technologies for training secondary school computer. To effectivelyorganize the performance of computer classes was shown the path of action of the consumer; to access the resources of the computer network of the university has been made role models. Spiritual outdated computer equipment based on the technology of "thick client" on standard personal computers and classes, as well as the current model of "zero client" that is based on the configuration of the class considered economically rational approach to the design of a computer class. To provide consumers with access to a converged network infrastructure computerclass University has developed a conceptual model. "Zero / thin client" or similarity of the technology "client" technology solutions customer network model was examined by organizational requirements infrastructure of computer classes.
Keywords: information technology; infrastructure; zero clients; fat and thin client virtualization